3D printing of graphene oxide/carbon nanotubes hydrogel circuits for multifunctional fire alarm and protection. (February 2023) - Chen, Xiaohu; Wang, Yanen; Zhang, Shan; Cui, Jiashu; Ma, Xinyu; Tian, Lidong; Li, Mingyang; Bao, Chengwei; Wei, Qinghua; Du, Bing
Abstract: Hydrogel circuit materials have a wide range of applications, especially in the field of flexible electronics. However, developing smart hydrogel circuit materials with remarkable properties remains a difficult problem. Based on the flexible design of circuit structure and direct inkjet 3D printing technology, we designed a printable conductive sodium alginate/graphene/carbon nanotube (SGC) ink and achieved three-dimensional graphene-based flexible circuits with high resolution and multifunction. Compared with previous work, the addition of GO, SWCNT and Ca 2+ make SGC have excellent conductivity and flame retardancy. The conductivity of SGC reaches 24.11S/m, which is 3 times higher than SA hydrogel. And the LOI is above 99.7%, which is far higher than most conductive polymer. We have conducted preliminary explorations and provided theoretical basis for the 3D printing of multifunctional SGC hydrogels with complex structures, which are expected to be applied in the field of flexible circuits, fire protection and artificial electronic skin. Highlights: A printable conductive sodium alginate/graphene/carbon nanotube (SGC) hydrogel. 3D printing SGC hydrogel with three dimensional complex structure. SGC can be used as electronic skin, fire protection and flexible circuit. SGC has excellent flame retardancy and pass UL-94 5VA ratings (LOI is above 99.7%).